Analysis of Visual Elements on the Movie Poster Suzume - Andreas Slamet Widodo; Ambar Mulyono; Kiki Fitaloka (TAMA: Journal of Visual Arts, 2023)
The poster was one of the visual media that served as a messenger primarily for the sense of sight to convey messages that needed visual communication and message symbols to be understood as well as for the promotion of the film. The study was intended to find out the meaning that visual elements posed on movie posters. The research methods used are qualitative descriptive analytics using the technique for collecting data for literature studies and observing the "Suzume" and semiotics film poster of Ferdinand De Saussure used as a research method to help researchers examine the visual and signature elements on the poster. Semiotics is the study of signs, bookmarks, and maps and the relation between them under a convention in the community. In the study, signs related to the film and visual posters are made beyond the reference to the movie scene.